The Role of Apps in Electroacoustic Music: A new dimension for music through tablets and other devices. - Chadabe, Joel (Organised Sound, 2015)
This article describes the potential of apps as a platform for composers of electroacoustic music to present their work. It traces a history of changing concepts of structure in music from objects and symmetrical forms to dynamic systems that provide a basis for interactive instruments. Early examples of interactive instruments are presented and discussed. The opening up of music to all sounds is discussed in the context of the origins and growth of global communities within the music world. The structure of an app format for electroacoustic compositions is described and examples of various music apps are discussed from the perspective of the electroacoustic app format.